PENGEMBANGAN BOOKLET INTERAKTIF IPS SEBAGAI MEDIA PENDUKUNG UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK SMP LABSCHOOL UNESA 1 - Alista Debby Ariyanti; Agung Stiawan; Asnimawati; Silvi Nur Afifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop an Interactive Social Studies Booklet and analyze its effectiveness in improving learning motivation among junior high school students. The study employed the Research and Development (R&D) method with the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The subjects were 26 students of class VII C of SMP Labschool UNESA 1. Data were collected through observation, interviews, expert validation, motivation questionnaires, and response questionnaires, and analyzed using the Wilcoxon Signed Rank Test and N-Gain test. The results showed that the interactive booklet achieved a good level of feasibility based on validation by media experts (80.21%) and material experts (93.75%). The use of the booklet also increased student learning motivation, as indicated by the Wilcoxon test results with a significance value of 0.000 (<0.05) and an N-Gain value of 0.41 (moderate category). Student responses (83.84%) and teachers (97.5%) were in the very good category. Thus, the Social Studies Interactive Booklet is suitable and quite effective for use as a learning support medium to increase students' learning motivation.